Subtract: ( 3b - 2c ) - ( 6c + 2b ) - ( b + c )

1 answer

To simplify the expression \((3b - 2c) - (6c + 2b) - (b + c)\), we will distribute the negative signs and combine like terms.

  1. Start with the expression: \[ (3b - 2c) - (6c + 2b) - (b + c) \]

  2. Distribute the negative sign: \[ 3b - 2c - 6c - 2b - b - c \]

  3. Now combine the like terms (the terms with \(b\) and the terms with \(c\)):

    • For the \(b\) terms: \(3b - 2b - b = 3b - 3b = 0\)
    • For the \(c\) terms: \(-2c - 6c - c = -2c - 6c - 1c = -9c\)
  4. Putting it all together: \[ 0 - 9c = -9c \]

Therefore, the simplified result is: \[ \boxed{-9c} \]